DUKUNGAN ORANG TUA DALAM MENENTUKAN STUDI LANJUT SISWA SMP: PERSPEKTIF DAN PENDEKATAN KONSELING KELUARGA - azizah, berta; Asna, Asna (Journal of Education Counseling, 2022)
Indonesia's compulsory education programme is for 12 years, starting from primary, junior secondary and senior secondary school levels as stipulated in Government Regulation No. 47/2008. For this reason, further schooling after junior high school must be implemented. In relation to further education after junior secondary school, this study discusses parental support for further education after junior secondary school. Overall, parental support aligned with the family counselling approach has the potential to create more inclusive, balanced and needs-based educational decisions. Thus, collaboration between parents, students, and counsellors is the main key in building a better future for students. The method used is the polling method by distributing questionnaires to students of SMP Negeri 2 Tulungagung class IX in the 2022/2023 academic year. The data collected are answers from 187 students (sample) who stated that parental support is important for continuing school after junior high school, parents provide advice or take part in determining the choice of further school after junior high school, your choice of school is the same as your parents' choice, parents support the school choice chosen by students, and further school after junior high school supports your future career plans.